Technology-Aided Interventions for Individuals With Autism: Implications for Policy and Practice. (October 2019) - Pham, Andy V.; Bennett, Kyle D.; Zetina, Heidy
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by pervasive difficulties in reciprocal social-communication skills and restricted, repetitive interests and behaviors. Advances in assistive technology can potentially improve the functional capabilities of individuals with ASD. This article reviews current legislation and professional standards related to educating students with ASD with an emphasis on technology and evidence-based practices. In particular, the article summarizes technology-aided interventions (e.g., speech-generating devices, computer-assisted instruction, video-based instruction, virtual reality, and robot-mediated interventions) that focused on social-communication skills among individuals with ASD. Implications and future directions of technology-aided interventions are discussed.